Pemberian Kredit Kendaraan Bermotor Menggunakan Metode Fuzzy Logic Sugeno Pada PT. Bintang Mandiri Finance Bekasi - ASEP PURNAMA ASEP PURNAMA (LPPM STMIK AL MUSLIM, 2022)
Bintang Mandiri Finance Bekasi is a leasing or financing company that provides loan funds with car BPKB guarantees. In terms of providing loan funds to customers, PT. Bintang Mandiri Finance Bekasi checks the data of prospective customers first, as a reference for creditworthiness. However, there are still many customers who have bad credit so that they are unable to pay their debt obligations to PT. Bintang Mandiri Finance Bekasi. The emergence of bad credit is caused at the beginning of the credit application process, the data provided by the prospective customer does not match the facts. This error occurs when conducting surveys and credit analysis which are still manually which have to check a lot of data provided by prospective customers. There is one way that can provide a solution, by using a system or artificial intelligence that can select prospective customers based on the desired criteria. Another part of Artificial Intelligence (AI) is Sugeno's Fuzzy logic. Sugeno's fuzzy logic is used to produce single/crisp decisions during defuzzification, its use depends on the problem domain that occurs and the design tool uses Unified Modeling Language (UML). The granting of credit using the Sugeno fuzzy logic method can be used in determining prospective customers based on the recommendation value of Sugeno's fuzzy logic calculations and can speed up the credit analysis process. The recommended value from the calculation of the Sugeno fuzzy logic method can minimize the occurrence of bad loans.